Management of Pulmonary Artery Aneurysm and Intracardiac Thrombus in a Young Male With Behçet’s Disease - Özgür Ulaş ÖZCAN,; Adalet GÜRLEK,; Görkem YILDIZ,; İrem Müge AKBULUT,; Eralp TUTAR,; Çetin EROL, (Archives of Rheumatology, 2014)
Pulmonary artery aneurysm associated with intracardiac thrombus is a rare complication of Behçet’s disease. In this article, we report a 26-yearold male admitted with massive hemoptysis. Pulmonary computed tomography angiogram demonstrated pulmonary artery aneurysm with thrombus. Echocardiography revealed a mobile right ventricular thrombus. The patient was treated with corticosteroids, cyclophosphamide, azathioprine, and colchicine without anticoagulant therapy. During follow-up, pulmonary artery aneurysm regressed, and no bleeding or thromboembolic event was observed.